2018
DOI: 10.1002/btpr.2653
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the biotechnological potential of a wild strain of Paraconiothyrium sp

Abstract: The isolation and characterization of fungal strains from poorly described taxa allows undercover attributes of their basic biology useful for biotechnology. Here, a wild fungal strain (CMU-196) from recently described Paraconiothyrium genus was analyzed. CMU-196 was identified as Paraconiothyrium brasiliense by phylogenetic analysis of the rDNA internal transcribed spacer region (ITS). CMU-196 metabolized 57 out of 95 substrates of the Biolog FF microplates. Efficient assimilation of dextrins and glycogen ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Moreover, metabolites like lignans, neolignans, and polyketides were identified in our study, but were rarely identified from the mycelia and fruiting bodies in previous studies (Muszynska et al 2011 ; Zhang et al 2015 ; Li et al 2016 ; Ren et al 2022 ), showing the metabolic differences between mycelial exudates, mycelia and fruiting bodies. Furthermore, compared to the separate culture modes, polyketides were generally repressed in C-G co-culture, which might be due to metabolic changes in response to biotic stimulus in the co-culture of Armillaria species with antagonism effect (Nicoletti et al 2004 ; Arredondo-Santoyo et al 2018 ; Dullah et al 2021 ). Lignans and neolignans, which were newly identified in our study, had significant bioactivities: lignans could inhibit the formation and growth of hormone-dependent cancer cells and protect the human body against oestrogen-related diseases, such as osteoporosis and breast cancer (Ionkova 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, metabolites like lignans, neolignans, and polyketides were identified in our study, but were rarely identified from the mycelia and fruiting bodies in previous studies (Muszynska et al 2011 ; Zhang et al 2015 ; Li et al 2016 ; Ren et al 2022 ), showing the metabolic differences between mycelial exudates, mycelia and fruiting bodies. Furthermore, compared to the separate culture modes, polyketides were generally repressed in C-G co-culture, which might be due to metabolic changes in response to biotic stimulus in the co-culture of Armillaria species with antagonism effect (Nicoletti et al 2004 ; Arredondo-Santoyo et al 2018 ; Dullah et al 2021 ). Lignans and neolignans, which were newly identified in our study, had significant bioactivities: lignans could inhibit the formation and growth of hormone-dependent cancer cells and protect the human body against oestrogen-related diseases, such as osteoporosis and breast cancer (Ionkova 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, P. brasiliense isolated from Himalayan yew produces paclitaxel, with antitumor activity [ 9 ]. Arredondo-Santoyo et al [ 10 ] showed that P. brasiliense expresses an activity antagonistic to Colletotrichum spp. and Phytophthora spp.…”
Section: Introductionmentioning
confidence: 99%